Deficiência intelectual e aprendizagem escolar: um estudo sobre práticas pedagógicas desenvolvidas em instituição privada que atende alunos de camadas sociais elevadas - Staudt, Luciane (2012)
The objective of this study is the identification and the curriculum analysis of the pedagogical work in a special school for students with intellectual disabilities from higher social strata, and it has the intention of verify what is the education work developed in this school and if this school presents any different kind of teaching. This investigation is based in a triple theoretical perspective, discussed in the first chapter, with the contributions of Apple (1989), Sacristán (1998) and Perrenoud (1993) about curriculum, scholar education and pedagogical activities. In the sequence the issues about the intellectual disability definitions and their relation with schooling process, which one of most contributors was Vigotski (1989). In the end we looking for to take the ownership of Bourdieu (2009) contributions in the field of high society schooling to analyze the relationship between schooling and intellectual disability. The hypothesis of this investigation, that the curriculum of a special school for high society students with intellectual disability differs from the others schools that doesn t have this focus, and its main function is the child development by an better appropriation of scholar contents, can not be proven because the scholar organization and the pedagogical practices, mainly based in routinization of activities and not by the exploration of the manifestation of the students, seem to express a fixed and unchanging perspective of cognitive impairments presented by students